Binuclear β-diketiminate complexes of copper(i). Issue 7 (30th January 2017) - Phanopoulos, Andreas; Leung, Alice H. M.; Yow, Shuhui; Palomas, David; White, Andrew J. P.; Hellgardt, Klaus; Horton, Andrew; Crimmin, Mark R.
Abstract : The reaction of a series of dinucleating bis(β-diketiminate) pro-ligands with mesitylcopper in the presence and absence of mono and diphosphines has allowed the isolation of a new series of dicopper(i ) complexes. Abstract : The reaction of a series of dinucleating bis(β-diketiminate) pro-ligands with mesitylcopper in the presence and absence of mono and diphosphines has allowed the isolation of a new series of dicopper(i ) complexes. Inclusion of trans -1, 2-cyclohexyl (1 ), 2, 6-pyridyl (2 ), and 2, 2′-oxydiaryl (3 ) spacers between the β-diketiminate units has been studied. The isolation of three new copper(i ) phosphine complexes[1·Cu2 (PPh3 )2 ], [2·Cu2 (PPh3 )2 ] and[3·Cu2 (PPh3 )2 ] is reported. While these compounds display large Cu⋯Cu separations of 5.4–7.9 Å in the solid state, solution data are consistent with a large degree of conformational freedom. Modification of the monophosphine to a diphosphine, DPPE, allowed the isolation of the novel 11-membered bimetallic macrocycle[2·Cu2 (DPPE)] containing both a binucleating nitrogen based ligand and a chelating diphosphine. While acetonitrile adducts of this series could also be generated in situ, under forcing conditions reaction of the 2, 6-pyridyl bridged ligand with mesityl copper led to the formation[2·Cu2 ]2 . This latter complex is a dimer of dicopper(i ) units in which the bis(β-diketiminate) ligand now binds four copper(i ) centers through not only the expected κ 2 - N, N ′-chelation but also κ 1 - and η 2 -binding of the central pyridine through orthogonal Cu–N and Cu–arene interactions. Reversible coordination of alkenes, pyridine and quinoline to the copper cluster was identified allowing the isolation and structural characterisation of a further series of dinuclear complexes[2·Cu2 (pyridine)2 ], [2·Cu2 (cyclopentene)2 ] and[2·Cu2 (norbornene)2 ] . Solution studies allow quantification of the reversible binding event through a van't Hoff analysis. Both solution and the solid state data suggest a weak anagostic interaction exists in the latter two alkene complexes of copper(i ). The new complexes have been characterized by X-ray diffraction, multinuclear NMR spectroscopy and CHN analysis.